2015
DOI: 10.1364/oe.23.007802
|View full text |Cite
|
Sign up to set email alerts
|

Metric of color-space coverage for wide-gamut displays

Abstract: Assessing the coverage of the color space of Recommendation ITU-R BT.2020 (Rec. 2020) has become increasingly important in the design of wide-gamut displays, and an appropriate metric for measuring the display gamut size is urgently needed. Display manufactures calculate the area ratios of their displays' RGB triangles to a standard RGB triangle in the CIE 1931 xy or CIE 1976 u'v' chromaticity diagram to indicate the displays' relative gamut size. However, they typically fail to mention which of the two diagra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 7 publications
1
30
0
Order By: Relevance
“…Higher correlations between the Rec. 2020 volume‐coverage ratios and the area‐coverage ratios in the xy diagram than between the same volume‐coverage ratios and the area‐coverage ratios in the u ′ v ′ diagram were also observed in the CIELUV L * u * v * space ( r = 0.985 for xy , r = 0.849 for u ′ v ′) and CIECAM02 Ja C b C space ( r = 0.969 for xy , r = 0.805 for u ′ v ′) . Furthermore, higher correlations were also found between the Rec.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Higher correlations between the Rec. 2020 volume‐coverage ratios and the area‐coverage ratios in the xy diagram than between the same volume‐coverage ratios and the area‐coverage ratios in the u ′ v ′ diagram were also observed in the CIELUV L * u * v * space ( r = 0.985 for xy , r = 0.849 for u ′ v ′) and CIECAM02 Ja C b C space ( r = 0.969 for xy , r = 0.805 for u ′ v ′) . Furthermore, higher correlations were also found between the Rec.…”
Section: Discussionmentioning
confidence: 67%
“…2020, Adobe RGB, DCI‐P3, and Rec. 709), yielding 11,880 different RGB primary sets in total . Note that the boundaries of the sample areas are not exhaustive in the definition of the wide gamut.…”
Section: Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Masaoka and Nishida found that the xy chromaticity areas for additive RGB displays were highly correlated with the 3D CGVs expressed in any of the CIE appearance spaces, including CIELAB, CIELUV (notwithstanding the u′v′ coordinates being precursors of the u*v* coordinates), and CIECAM02. In these color appearance models, the chroma increases as the lightness increases, and it was accidentally found that enlarged yellow and green regions in the xy diagram are suitable for use as a CGV metric .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the u′v′ chromaticity areas do not exhibit any significant correlation with the 3D CGVs in any color appearance space. Although the u′v′ diagram has gained popularity among display engineers and color scientists for measuring the chromaticity gamut area (often inappropriately referred to as color gamut), owing to its nominal uniformity, we cannot ignore the fact that the u′v′ area ratio to a reference color space, such as sRGB, is usually larger than the xy area ratio …”
Section: Introductionmentioning
confidence: 99%